ACCESSIBILITY AND REPRESENTATION OF WEST KALIMANTAN LOCAL CONTENT IN CLASSIC LITERATURE TEXTBOOKS - Herlina; Dini Hajjafiani (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2025)
The purpose of this research was to know the accessibility and the respresentativeness of local content in text book that used in the lecturer class of Sastra Klasik Kalimantan Barat. This research used descriptive qualitative research. Data collected by using questionnaire to 60 students who have already attended this class. This research is done for students of Indonesian Education and Literature Study Program of IKIP PGRI Pontianak. The results of the research were 34,2% students said that it was difficult to access of text book and there were 1,8% students said that it was easy, there were 33% students said that it was not represented and there were 9% students said it was represented. The conclusion of this research was the accessibility and the representativeness of text book had negative response by some students.